Physicochemical Properties and Rheological Behavior of Gluten-Free Flour Blends for Bakery Products - Ike, Charles (Journal of Food Sciences, 2024)
Purpose: The general aim of the study was to investigate the physicochemical properties and rheological behavior of gluten-free flour blends for bakery products. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to physicochemical properties and rheological behavior of gluten-free flour blends for bakery products. Preliminary empirical review revealed that hydrocolloids such as xanthan gum and guar gum significantly improved dough viscoelasticity, texture, and stability, while the efficacy of carrageenan was limited. Optimizing the concentrations and combinations of hydrocolloids was deemed essential for achieving superior rheological properties. Additionally, the study emphasized the importance of considering physicochemical properties alongside rheological behavior to develop gluten-free bakery products that meet consumer expectations. Overall, the findings highlighted the complexity of gluten-free baking and underscored the need for a multidimensional approach integrating physicochemical analyses with rheological assessments. Unique Contribution to Theory, Practice and Policy: The Food Material Science theory, Rheology theory and Biopolymer theory may be used to anchor future studies on physicochemical properties and rheological behavior of gluten-free flour blends. The study provided valuable recommendations. It contributed to theory by exploring the effects of various hydrocolloids on dough properties, highlighting the importance of xanthan gum and guar gum in improving dough viscoelasticity. In practice, it suggested optimizing hydrocolloid concentrations for superior rheological properties in gluten-free bakery products. Moreover, the study offered insights for policy-makers regarding the formulation of gluten-free bread to meet quality standards. Overall, the research advanced understanding in the field and provided practical guidelines for industry and policymakers.